First branchial cleft fistula: a case report and literature review - Razan Bawazir; Abdullah Bawazir; Osama Bawazir (SpringerOpen, 2021)
Abstract Background First branchial cleft fistula is a rare malformation of the neck and head. The purpose of this report is to showcase a method of treating first brachial cleft fistula while preserving the facial nerve. Case presentation This case report presents an 8-year-old female with a type 2 first branchial cleft fistula. The treatment process follows multidisciplinary approach with the aid of health professionals from different departments, pre-op magnetic resonance imaging (MRI) scanning to map the fistula, and the use of nerve monitoring device (NIM). Conclusion The procedure was successfully done while preserving the facial nerve.